Economic and thermodynamic study of different cooling options: A review. (September 2016) - Gupta, A.; Anand, Y.; Tyagi, S.K.; Anand, S.
Abstract: A large share of the total conventional energy generation from fossil fuels gets consumed for cooling and heating applications to maintain the thermal comfort of the individuals. The different cooling equipments during the operation also generate the losses which in turn reduces the overall performance of the systems. The present study therefore is based on the review of various thermodynamic and economic parameters that can be controlled in cooling machine to optimize the performance as well as to check the economic feasibility of the system. The different advanced methodologies to analyze the performance of the system along with different energy storage strategies have also been analyzed in the study. The review study clearly stressed on the fact that renewable energy sources are the best suitable options to run cooling systems provided they are well integrated and managed according to the suitable operational parameters. The economic study however, strictly points that the installed system must be economically feasible in terms of deciding economic parameters like net present worth (NPW), discounted pay back (DPB), capital recovery factor (CRF), etc. Besides, the present study also reveals that the check on irreversibility helps in improving the economy of the system.